Dinamika Hukum Islam dalam Modernisasi Masyarakat Muslim Indonesia Kontemporer - Baihaqi, Baihaqi (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
Islamic law in Indonesia develops dynamically within a diverse social reality, particularly among the stratified Muslim communities of santri, priyayi, and abangan. This article analyzes how modernization and globalization influence the religious practices of these three groups and how Islamic law responds to these changes through the framework of maqāṣid asy-syarī‘ah. Using an Islamic legal sociology approach and a qualitative-descriptive method, this study examines the role of ijtihad and the reinterpretation of Islamic law in maintaining its relevance amidst social transformation. The findings indicate that the santri group tends to adhere to classical fiqh-based religious practices, while the priyayi adopt a more culturally adaptive approach, and the abangan exhibit a syncretic understanding of Islam. Within the maqāṣid sharī‘ah perspective, Islamic law continues to evolve to ensure public welfare, justice, and a balance between traditional values and modernization demands. Therefore, a contextual understanding of Islamic law is essential in addressing the challenges of social change in Indonesia.